Fungal keratitis in Iran: Risk factors, clinical features, and mycological profile - Soleimani, Mohammad; Izadi, Alireza; Khodavaisy, Sadegh; Santos, Claudy Oliveira dos; Tehupeiory-Kooreman, Marlou C.; Ghazvini, Roshanak Daie; Hashemi, Seyed Jamal; Mousavi, Seyed Amin Ayatollahi; Aala, Farzad; Abdorahimi, Mahsa; Aminizadeh, Mehdi; Abedinifar, Zohre; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
This study was intended to investigate the clinical features and predisposing factors of fungal keratitis (FK), as well as molecular identification and antifungal susceptibility of causative agents in Tehran, Iran. This cross-sectional study was carried out from April 2019 to May 2021. All fungi isolates were identified using conventional methods and were confirmed by DNA-PCR-based molecular assays. Matrix-assisted laser desorption/ionization-time of flight (MALDI-TOF) was used to identify yeast species. Minimum inhibitory concentrations (MIC) of eight antifungal agents were assessed according to the European Committee on Antimicrobial Susceptibility Testing (EUCAST) microbroth dilution reference method. Fungal etiology was confirmed in 86 (7.23%) of 1189 corneal ulcers. A significant predisposing factor for FK was ocular trauma caused by plant materials. Therapeutic penetrating keratoplasty (PKP) was required in 60.4% of cases. The predominant fungal species isolated was Fusarium spp. (39.5%) followed by Aspergillus spp. (32.5%) and Candida spp. (16.2%). The MIC results indicate that amphotericin B may be appropriate for treating FK caused by Fusarium species. FK caused by Candida spp. can be treated with flucytosine, voriconazole, posaconazole, miconazole, and caspofungin. In developing countries such as Iran, corneal infection due to filamentous fungi is a common cause of corneal damage. In this region, fungal keratitis is observed primarily within the context of agricultural activity and subsequent ocular trauma. Fungal keratitis can be managed better with understanding the "local" etiologies and antifungal susceptibility patterns.